Baroreflex activation therapy in patients with heart failure with reduced ejection fraction: a single‐centre experience - Carola Blanco; Tomas Madej; Norman Mangner; Jennifer Hommel; Susanna Grimm; Michael Knaut; Axel Linke; Ephraim B. Winzer (ESC Heart Failure, 2023)
Abstract Aims Heart failure with reduced ejection fraction (HFrEF) is associated with excessive sympathetic and impaired parasympathetic activity. The Barostim Neo™ device is used for electronical baroreflex activation therapy (BAT) to counteract autonomic nervous system dysbalance. Randomized trials have shown that BAT improves walking distance and reduces N‐terminal prohormone of brain natriuretic peptide (NT‐proBNP) levels at least in patients with only moderate elevation at baseline. Its impact on the risk of heart failure hospitalization (HFH) and death is not yet established, and experience in clinical routine is limited. Methods and results We report on patient characteristics and clinical outcome in a retrospective, non‐randomized single‐centre registry of BAT in HFrEF. Patients in the New York Heart Association (NYHA) Classes III and IV with a left ventricular ejection fraction (LVEF) <35% despite guideline‐directed medical therapy were eligible. Symptom burden, echocardiography, and laboratory testing were assessed at baseline and after 12 months. Clinical events of HFH and death were recorded at routine clinical follow‐up. Data are shown as number (%) or median (inter‐quartile range). Between 2014 and 2020, 30 patients were treated with BAT. Median age was 67 (63–77) years, and 27 patients (90%) were male. Most patients (83%) had previous HFH. Device implantation was successful in all patients. At 12 months, six patients had died and three were alive but did not attend follow‐up. NYHA class was III/IV in 26 (87%)/4 (13%) patients at baseline, improved in 19 patients, and remained unchanged in 5 patients (P < 0.001). LVEF improved from 25.5 (20.0–30.5) % at baseline to 30.0 (25.0–36.0) % at 12 months (P = 0.014). Left ventricular end‐diastolic diameter remained unchanged. A numerical decrease in NT‐proBNP [3165 (880–8085) vs. 1001 (599–3820) pg/mL] was not significant (P = 0.526). Median follow‐up for clinical events was 16 (10–33) months. Mortality at 1 (n = 6, 20%) and 3 years (n = 10, 33%) was as expected by the Meta‐Analysis Global Group in Chronic Heart Failure risk score. Despite BAT, event rate was high in patients with NYHA Class IV, NT‐proBNP levels >1600 pg/mL, or estimated glomerular filtration rate (eGFR) <30 mL/min at baseline. NYHA class and eGFR were independent predictors of mortality. Conclusions Patients with HFrEF who are selected for BAT are in a stage of worsening or even advanced heart failure. BAT appears to be safe and improves clinical symptoms and—to a modest degree—left ventricular function. The risk of death remains high in advanced disease stages. Patient selection seems to be crucial, and the impact of BAT in earlier disease stages needs to be established.